Facial trauma in a softball player - Patterson, B. L.; Anan, T. (The Physician and Sportsmedicine, 2003)
Facial trauma frequently results in fracture of the facial bones. A blowout fracture involves the eye orbit and usually transpires when the object hitting the eye (eg, baseball, softball, fist, elbow) is larger than the orbit itself. The mechanism of injury will provide the physician with a clue to the diagnosis. Prompt recognition of any significant complications, proper imaging, and referral to an ophthalmology specialist are usually required. Facial reconstruction by a plastic surgeon may also be necessary.